ELABORACIÓN DE UN PLAN ESTRATÉGICO PARA LA REDUCCIÓN DE PÉRDIDAS COMERCIALES EN LA EMPRESA ELÉCTRICA REGIONAL DEL SUR S.A. (EERSSA)" - ERREYES TOCTO, DARÍO JAVIER (2019)
This study began with the idea of improving standards billing electricity service provided by the EERSSA, in order to reduce commercial losses of energy. Commercial energy losses occur due to theft, fraud or mismanagement (errors in taking readings, calculation). The methodology used, left to perform an internal analysis of the headquarters of turnover of the company, which has within its powers to take readings and billing of consumption concept of electric service customers in the concession area of EERSSA . Also the analysis of head of fundraising, head of agencies, superintendence power control and superintendence of facilities was conducted. An analysis of external factors was performed to determine the status of EERSSA against electric distribution companies in the country, number of customers, concession area, handling the same commercial software are comparable. With the information obtained, matrices Internal Factors (EFI) and External Factors (EFE) rose, giving a quantification and values for the analysis of situation of the company. Whereas companies that have similar characteristics with EERSSA Competitive Profile Matrix was built. With this background the strategic objectives to reduce the rates of commercial energy losses, Value Chain analysis and subsequent preparation of the Annual Operating Plan (AOP) were determined. The state of affairs of the company, contains the internal analysis and the factors that influence the rates of commercial energy losses and customer satisfaction, allowing to establish a 7 fortress knowledge of the electricity sector and claims attended or reported. As for weaknesses was determined that there staff unknown how commercial energy losses arising, as well as high percentages of poor care claims for billing. After analyzing the environment was determined to show favorable economic conditions country and agreement regarding new policies adopted power and changing the productive matrix in the country. Mission, Vision and Values: With these considerations, the proposed Strategic Plan which defines the philosophical elements of the South Regional Electric Company as are structured. Also aimed at improving management indices in reducing commercial losses of energy, compliance with quality standards in the monthly billing customers, as well as elements that differentiate and generate a competitive advantage and strategic objectives are proposed offering added value to its customers. The proposed strategies also aim to improve processes lecturación, billing and marketing; without neglecting the empowerment of human talent. The POA establishes the strategic actions to be followed by EERSSA and run for the period 2015-2019, determines the areas responsible for development and formulates indicators for monitoring and evaluation of compliance.